2015
DOI: 10.1016/j.ijsu.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the bending of the tip of elastic stable intramedullary nails on removal and associated complications in pediatric both bone forearm fractures: A pilot study

Abstract: Level III—retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…TEN with a diameter of 2.5 mm is recommended for children aged 6-10 years, and 3.0-3.5 mm is recommended for children over 10 years; (ii) the thicker the TEN, the stronger the elasticity and fixation. However, the difficulty of insertion will increase; and (iii) postoperative irritability reaction around nails should be watched 42,43 .…”
Section: Clinical Experience For Treating Pediatric Humeralmentioning
confidence: 99%
“…TEN with a diameter of 2.5 mm is recommended for children aged 6-10 years, and 3.0-3.5 mm is recommended for children over 10 years; (ii) the thicker the TEN, the stronger the elasticity and fixation. However, the difficulty of insertion will increase; and (iii) postoperative irritability reaction around nails should be watched 42,43 .…”
Section: Clinical Experience For Treating Pediatric Humeralmentioning
confidence: 99%
“…Cutting and bending the nail under the skin and above the level of the tendon helps to reduce the risk of skin irritation. [ 24 ] Reviewing the literature and our experiences we came to the conclusion that optimisation of the insertion point and the position of the extraosseal end of the nails can reduce the risk of both acute and chronic ruptures. Intraoperative ultrasound has been proven an easy and useful tool for visualizing these optimal reference points.…”
Section: Discussionmentioning
confidence: 99%
“…Flynn et al [39] reported rupture of the EPL tendon due to an injury from the ESIN in 2 of 103 patients (1.9%), which is close to our rate of 1.5%. Gibbon et al [40] recently published an investigation recommending bending of the ESIN tip and suggested tip bending of 180° before burying to prevent skin irritations and additional procedures. Only 1 superficial wound infection at the radial insertion point occurred after implant removal and was locally treated; no deep infection was observed even after open fractures.…”
Section: Discussionmentioning
confidence: 99%